Does heating stimulate germination in Leptospermum scoparium (mānuka; Myrtaceae)?. Issue 4 (2nd October 2017) - Battersby, Paul F.; Wilmshurst, Janet M.; Curran, Timothy J.; Perry, George L. W.
ABSTRACT: Fire regimes are powerful selective filters. In New Zealand, fire activity was rare before human settlement, and New Zealand's indigenous woody flora shows little adaptation to frequent fire. One of the few woody indigenous species to show adaptation to frequent fire is Leptospermum scoparium (Myrtaceae), a Plio-Pleistocene immigrant from Australia. Leptospermum scoparium is a widespread early-successional shrub to small tree that frequently dominates post-fire successions, and shows geographically-variable pyriscent serotiny, a fire-adaptation in which seeds are retained in the canopy and open post-fire. Another widespread reproductive adaptation to fire is heat-stimulated germination. Some Australian Leptospermum respond positively to heat treatment, and observations in New Zealand suggest that the seeds of L. scoparium within thick-walled capsules open immediately after fire and successfully germinate, indicating at least no deleterious effect of heating. In some fire-prone systems such as Mediterranean shrublands, traits such as serotiny and heat-stimulated germination have been positively associated with traits associated with flammability (e.g. retention of dead fuel). Here we evaluate the effect of heat stimulation (short exposure to high temperatures) of capsules on germination in L. scoparium from New Zealand, and evaluate links between germination, serotiny and shoot-level flammability. Germination trials using seed collected from 12 populations indicated no consistent positive or negative effect of heat treatment on germination success (germinability). These trials suggest that the capsules of L. scoparium at least provide adequate insulation to heating. Germinability was not consistently related to either serotiny or flammability; nor was it related to latitude or elevation. While taxa from other fire-prone ecosystems may show coordinated trait responses to fire, the lack of association between physical measures of flammability and germination rates indicate that this is not the case in L. scoparium, New Zealand's most fire-adapted indigenous woody species.